Breaking the Silence: An Islamic Legal Approach to Facilitating Reporting and Testimony by Muslim Victims and Witnesses of Sexual Crimes - Julie Lowe (Religions, 2022)
Many Muslims hold the doctrine of the legal schools (madhāhib) in high esteem. As such, the schools’ approaches to rape and sexual assault may impact the behaviour of Muslim victims and witnesses. Through an examination of the legal rules that regulate rape and sexual assault in fiqh and fatwā works associated with the four Sunni schools and Ibn Ḥazm, I aim to determine whether the relevant rules may interfere with the willingness of Muslim victims and witnesses to report or testify to sexual crimes. I argue that although the jurists’ prosecution of sexual assault as a discretionary offence (taʿzīr) is compatible with reporting and testimony, their prosecution of rape as coerced illicit intercourse (zinā), usurpation (ghaṣb), or banditry (ḥirāba) silences victims and witnesses. Further, rules related to financial compensation do not encourage victims to come forward. Reclassifying rape as a discretionary offence would better promote reporting and testimony by victims and witnesses. The central role of ijtihād in creating the historical rules on rape, the jurists’ intent behind those rules, and modern knowledge regarding the reality of rape support this reclassification. Fully resolving issues related to civil compensation is difficult without broader reforms of Islamic tort law.